2009
DOI: 10.1073/pnas.0807614106
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule plus-end tracking by CLIP-170 requires EB1

Abstract: Microtubules are polarized polymers that exhibit dynamic instability, with alternating phases of elongation and shortening, particularly at the more dynamic plus-end. Microtubule plus-end tracking proteins (؉TIPs) localize to and track with growing microtubule plus-ends in the cell. ؉TIPs regulate microtubule dynamics and mediate interactions with other cellular components. The molecular mechanisms responsible for the ؉TIP tracking activity are not well understood, however. We reconstituted the ؉TIP tracking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
181
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(202 citation statements)
references
References 42 publications
(61 reference statements)
19
181
2
Order By: Relevance
“…EBs have been shown to autonomously bind to MTs, while many other +TIPs require EBs for proper MT binding and/or tip localization (Dixit et al, 2009;Akhmanova and Steinmetz, 2010;Slep, 2010;Li et al, 2011b). While we found SPR1 to behave like other +TIPs in that it physically interacts with EB1b, our data show that SPR1 can function, at least in part, autonomously of EB1b.…”
Section: Discussionmentioning
confidence: 99%
“…EBs have been shown to autonomously bind to MTs, while many other +TIPs require EBs for proper MT binding and/or tip localization (Dixit et al, 2009;Akhmanova and Steinmetz, 2010;Slep, 2010;Li et al, 2011b). While we found SPR1 to behave like other +TIPs in that it physically interacts with EB1b, our data show that SPR1 can function, at least in part, autonomously of EB1b.…”
Section: Discussionmentioning
confidence: 99%
“…The binding process of CLIP-170 is rather complex and details can be found in [207,38,37,99,96]. Here, we just notice that CLIP-170 temporarily binds to the plus-end of MTs and is released with a given rate.…”
Section: Regulation Of the Microtubule Dynamicsmentioning
confidence: 99%
“…The properties of the motors could be changed by the viscoelasticity of the cytoplasm (in a similar way as it has been shown that mechanical properties of MTs can be quite different in a viscoelastic medium [53]). Complementary proteins, as for example the tau protein, exist which can bind to MTs and reduce the binding affinity of molecular motors [96]. The attachment rate could also be influenced by regulatory proteins binding directly to the head region of molecular motors [244].…”
Section: In Vitro Versus In Vivomentioning
confidence: 99%
“…histidine or glutathione S-transferase), but the tags and purification strategies differ. Some studies used proteins with the tags left intact (26 -28), whereas others used tag-cleaved proteins (19,24,29,30). In some cases where the tags were cleaved off, several amino acids still remained after the main tag was removed.…”
Section: Microtubules (Mts)mentioning
confidence: 99%